Real-Time Linux Analysis Using Low-Impact Tracer. (5th June 2014) - Rajotte, François; Dagenais, Michel R.
Abstract : Debugging real-time software presents an inherent challenge because of the nature of real-time itself. Traditional debuggers use breakpoints to stop the execution of a program and allow the inspection of its status. The interactive nature of a debugger is incompatible with the strict timing constraints of a real-time application. In order to observe the execution of a real-time application, it is therefore necessary to use a low-impact instrumentation solution. Tracing allows the collection of low-level events with minimal impact on the traced application. These low-level events can be difficult to use without appropriate tools. We propose an analysis framework to model real-time tasks from tracing data recovered using the LTTng tracer. We show that this information can be used to populate views and help developers discover interesting patterns and potential problems.